High-Transmittance Subwavelength Metal Grating with Relief Structure Composed of Multiple Steps - Zhongfei Wang; Dawei Zhang; Qi Wang; Banglian Xu; Qingyong Tang; Yuanshen Huang; Songlin Zhuang (The Scientific World Journal)
A new kind of subwavelength metal grating with relief structure is designed and analyzed, in which the shape of the grating lines is no longer a single rectangle, but a relief structure with multiple steps. GsolverV52 was used to determine the optimal values of the grating period, groove depth, and the number of steps. The optical performance of the novel structure is evaluated and compared in terms of the transmission efficiency and extinction ratio over the visible and near-infrared wavelength spectrum. It is shown that, in the near-infrared band, the maximum transmittance can be increased about 15% compared to the traditional metal grating under the same parameters. With the unique characteristics, the metal grating is expected to find applications in liquid crystal display fields, polarization imaging, optical communication, and so on.